Reversible Hydration Composite Films for Evaporative Perspiration Control and Heat Stress Management - Yang, Jiachen; Zhang, Xueping; Koh, J. Justin; Deng, Rensheng; Kumarasamy, Saravana; Xu, Yuan Xing; Qu, Hao; Zhang, Songlin; Zhang, Yaoxin; Tan, Swee Ching (Small (Weinheim an der Bergstrasse, Germany), 2022)
Donning of personal protective equipment (PPE) in the healthcare sector has been intensified by the on‐going COVID‐19 pandemic around the globe. While extensive PPE provides protection, it typically limits moisture permeability and severely hinders the sweat evaporation process, resulting in greater heat stress on the personnel. Herein, a zinc‐poly(vinyl alcohol) (Zn‐PVA) composite film is fabricated by embedding a super‐hygroscopic zinc‐ethanolamine complex (Zn‐complex) in the PVA matrix. By attaching the Zn‐PVA composite film, the relative humidity (RH) inside the protective suit decreases from 91.0% to 48.2%. The reduced RH level, in turn, enhances evaporative cooling, hence bringing down the heat index from 64.6 to 40.0 °C at an air temperature of 35 °C, remarkably lowering the likelihood of heat stroke. The American Society for Testing and Materials tests conducted on a sweating manikin have also proven that the Zn‐PVA composite films can significantly reduce the evaporative resistance of the protective suit by 90%. The low material cost, facile fabrication process, and reusability allow the Zn‐PVA composition films to be readily available for healthcare workers worldwide. This application can be further extended to other occupations that are facing severe thermal discomfort and heat stress. A super‐hygroscopic zinc‐poly(vinyl alcohol) composite film is developed to improve thermal comfort for healthcare workers. With the composite film attached to the personal protective equipment, the water vapor accumulated is rapidly absorbed by the film. A steep vapor pressure gradient is created to facilitate sweat evaporation and relieve the heat stress experienced by healthcare workers.